2021
DOI: 10.1002/aesr.202100083
|View full text |Cite
|
Sign up to set email alerts
|

Porous Bilayer Electrode‐Guided Gas Diffusion for Enhanced CO2 Electrochemical Reduction

Abstract: Comparing with the massive efforts in developing innovative catalyst materials system and technologies, structural design of cells has attracted less attention on the road toward high‐performance electrochemical CO2 reduction reaction (eCO2RR). Herein, a hybrid gas diffusion electrode‐based reaction cell is proposed using highly porous carbon paper (CP) and graphene aerogels (GAs), which is expected to offer directional diffusion of gas molecules onto the catalyst bed, to sustain a high performance in CO2 conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Others have also found that ionic liquid environments enhance the selectivity of CO 2 reduction toward CO as well as higher-order hydrocarbons . Additional examples of environmental engineering include selection of electrolyte molecules and morphology of catalyst materials. However, because CO 2 reduction usually involves protons, the effects of the local environment of the proton donor, such as H 2 O, require further scrutiny as even minute quantities of H 2 O in bulk solvent can play a crucial role in electrochemical CO 2 reduction. , One of the main challenges in probing the local environment of H 2 O during electrochemical CO 2 reduction in aqueous electrochemical systems is the competition between CO 2 reduction and the hydrogen evolution reaction (HER) from H 2 O reduction, reactions that occur over a similar potential range. Further, because of the significantly higher concentration of H 2 O compared to CO 2 in aqueous media, the HER can dominate and overwhelm the CO 2 reduction reaction. , …”
Section: Bulk Co2 Reduction In Acetonitrilementioning
confidence: 99%
“…Others have also found that ionic liquid environments enhance the selectivity of CO 2 reduction toward CO as well as higher-order hydrocarbons . Additional examples of environmental engineering include selection of electrolyte molecules and morphology of catalyst materials. However, because CO 2 reduction usually involves protons, the effects of the local environment of the proton donor, such as H 2 O, require further scrutiny as even minute quantities of H 2 O in bulk solvent can play a crucial role in electrochemical CO 2 reduction. , One of the main challenges in probing the local environment of H 2 O during electrochemical CO 2 reduction in aqueous electrochemical systems is the competition between CO 2 reduction and the hydrogen evolution reaction (HER) from H 2 O reduction, reactions that occur over a similar potential range. Further, because of the significantly higher concentration of H 2 O compared to CO 2 in aqueous media, the HER can dominate and overwhelm the CO 2 reduction reaction. , …”
Section: Bulk Co2 Reduction In Acetonitrilementioning
confidence: 99%
“…These results indicate that PCCNS-20 has the highest active site volumetric density and strong mass/charge transport capability. [40] We further analyzed the rotating ringdisk electrode (RRDE) results to calculate the electron transfer number (n) and the peroxide species yield (H 2 O 2 %). In Figure 5d, the n value of the PCCNS-20 is identified between 3.98 and 4.00 at the potential range of 0.2-0.8 V, almost the same as the commercial Pt/C.…”
Section: Resultsmentioning
confidence: 99%
“…COMSOL simulation on CO 2 molar concentration along the cathode catalyst layer for (N) CP‐cell, (O) GA‐cell, and (P) GACP‐cell. Reproduced with permission: Copyright 2021, John Wiley & Sons, Inc 64 …”
Section: Progress Of the Electrolyzer Used For Co2 Reductionmentioning
confidence: 99%
“…Liu et al 63 designed a porous hybrid bilayer GDEs that achieve the FE $ 94% of CO than H-cell $ 60%. Traditional GDEs consists of catalyst layer and gas diffusion layer that the catalysts uniformly coated on the carbon 64 paper with the average thickness of 10 μm (Figure 4H-J). However, the traditional GDEs structure will destroy after a long-term reaction and the electrolyte will block the CO 2 mass transfer pathway.…”
Section: Liquid Flow Cellsmentioning
confidence: 99%